User participation behaviour in crowdsourcing initiatives: influencing factors, related theories and incentive strategies. (19th November 2021) - Zhang, Xu; Peng, Zhanglin; Zhang, Qiang; Lu, Xiaonong; Song, Hao
Crowdsourcing is a powerful paradigm that leverages collective intelligence to solve problems. Good performance in crowdsourcing initiatives depends on energetic user participation. This paper reviews and analyses the current existing research works that are related to user behaviour in crowdsourcing initiatives. Particular attention is paid to the following aspects. First, we summarise the influencing factors of user participation behaviour in crowdsourcing initiatives. Second, we review the related behaviour theories to further understand the relationship between these factors and user behaviour. Third, we generalise about incentive strategies from the perspective of requesters and crowdsourcing platforms. Finally, the research directions of user behaviour in crowdsourcing initiatives are discussed in this study.